(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
By examining firm pressure with two metal instruments on teeth, the extent of vertical and horizontal displacement considered as tooth mobility, which is due to either periodontal disease or trauma. Nowadays teeth mobility is a common problem in dental scenarios, which results inocclusal problems, Dietary problems, and disturbances in mastication, aesthetic problem and worsening life quality. The treatment of tooth mobility is based on its etiology; it may be surgical or non-surgical. Surgically by Periodontal surgery, non-surgically by occlusal adjustment and splinting. Sometimes the Occlusal adjustment can be done by the surgical process. In the article, we discuss the cause of tooth mobility, relation between tooth mobility and occlusion including indication, contraindication and principles of tooth splinting. Our ultimate goal is to restore mastication function, good aesthetic, to improve patient comfort and good oral functions by various periodontal treatments for the management of mobile teeth.